“How can I get into the city center?”—pragmatic strategies at use in international tourism interactions in Croatia - Vida-Mannl, Manuela (Frontiers in Communication, 2024)
In Croatia, speaking many different languages is popular and perceived as a prestigious abilityskill. English is one of the most commonly spoken additional languages and many Croats engage with it frequently, e.g. when watching undubbed American or British TV programs and movies. Due to this frequent engagement as well as the rise of English as a global language, especially younger Croats and those who work in the tourism sector tend to be quite proficient users of English. Similar to other lingua franca contexts, wWhen interacting with tourists, Croats use accommodation strategies to cater to the tourists' linguistic needs to increase understanding and communicative success (cf., e.g., Kaur 2022 on pragmatic strategies). The present investigation centers on the specific pragmatic strategies present in such interactions between international tourists and local tourism workers and, based on a subset of 48 conversations recorded at the Franjo Tuđman Airport Zagreb, it illustrates the pragmatic strategies in the relational negotiation of directions to the city center. It shows that tourists and tourism workers tend to use the investigated pragmatic strategies in the following order of frequency: SMs>DMs>HMS>repetition>rephrasing>other features. However, taking a closer look, the study unveils how tourism workers balance the need for efficiency and sociability when engaging with international tourists and offers a first take at understanding why the answers to similar questions often vary and that shows that the quality and quantity of the provided answers are influenced not only by linguistic factors.